D+ hemolytic uremic syndrome - Ni Made Sumiartini; I Nyoman Lila; I Ketut Suarta (Paediatrica Indonesiana, 2004)
Hemolytic uremic syndrome (HUS) is characterized by anemia microangiopathy, thrombocytopenia, and acute renalfailure, predominantly occurs in childrenyounger than 4 years of age. It is the most commoncause of acute renal failure in children.1,2 HUS is dividedinto two categories, the epidemic type which isaccompanied by enteritis (D+HUS) and the sporadictype which is not accompanied by enteritis (D-HUS).The pathogenesis is unknown, but available evidencestrongly suggests endothelial cell damage in the organs.